Gabelentz and the science of language - McElvenny, James ca. 20./21. Jh (Amsterdam University Press, 2020)
The German sinologist and general linguist Georg von der Gabelentz (1840-1893) occupies an interesting place at the intersection of several streams of linguistic scholarship at the end of the nineteenth century. As professor at the University of Leipzig and then at the University of Berlin in the final decades of the nineteenth century, Gabelentz was present at the main centers of linguistic scholarship at the time. He was, however, generally critical of the narrow, technical focus of mainstream historical-comparative linguistics as practiced by the Neogrammarians and instead emphasized approaches to language inspired by a line of researchers stemming from Wilhelm von Humboldt (1767-1835). Gabelentz' alternative conception of linguistics led him to several pioneering insights into language that informed linguistic research in the wake of the structuralist revolution. This volume brings together four essays that explore Gabelentz' contribution to linguistics from a historical perspective. In addition, it makes one of Gabelentz' key theoretical texts, "Content and Form of Speech", available to an English-speaking audience for the first time